Are varus knees contracted? Reconciling the literature - McAuliffe, Michael J; Vakili, Ali; Garg, Gautam; Roe, John; Whitehouse, Sarah L; Crawford, Ross (Journal of orthopaedic surgery (Hong Kong), 2017)
Purpose: There is direct literature conflict regarding coronal plane contracture or laxity in the end-stage varus osteoarthritic knee. Understanding the preoperative soft tissue status is important for optimizing the soft tissue envelope during total knee arthroplasty (TKA). Methods: The lower limb was manipulated using computer navigation, prior to surgical releases, to allow the limb weight-bearing axis to pass through the knee centre in maximum extension and 20° of flexion. Coronal plane laxity was measured in 78 varus (−7.7° ± 2.8°) knees as medial and lateral displacement from this point and compared to published values for healthy subjects. Results: Medial contracture was present in 12.8% (10/78) of the knees. Of these 10 knees, 5 displayed abnormal lateral laxity. Knees with a contracture in maximum extension also displayed a significant decrease (p < 0.0001) in medial laxity at 20° of flexion compared to non-contracted knees. In maximum extension, 19.2% (15/78) of knees had abnormally increased lateral laxity, 10 did not have a medial contracture. The remaining five knees with increased lateral laxity or 6.4% (5/78) of the total cohort also displayed a medial contracture. Lateral laxity increased significantly with increasing varus deformity. Medial laxity did not significantly decrease when comparing varus deformity of 5–10° versus >10°. Conclusion: The majority of varus knees with deformity of up to 15° have neither a medial contracture nor abnormal lateral laxity when referenced to the individualized neutral axis of the knee. Surgical releases during TKA should be uncommon. Medial contracture when present is influenced by both posterior and medial structures. Lateral laxity is a more consistent feature of the varus knee. The patterns of contracture and laxity are variable with limited correlation to deformity.